ThinkEPI based on questions - Calderón-Rehecho, Andoni (Anuario ThinkEPI, 2018)
Questions are proposed for helping to think about the information world and the libraries.
Keywords: Librarians; Libraries; Universities; Information management; Research; Science; Open Access; Digital publishing; Artificial intelligence; Big data.